Neuroprotective effect of Emblica on enhancing memory in scopolamine induced memory impaired Long Evans Rats - Rashid, Md Jabir Ben; Amin, Ruhul; Salam, Sarmin; Islam, Saiful; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2025)
Background: Alzheimer’s disease is the commonest cause of progressive loss of memory and dementia due to oxidative stress. Various constituents of Amloki (Phyllanthus emblica or PE) fruit including phenols, tannoid,tannin and vitamin C counteract the oxidative stress and protect memory. Objective: To investigate the capacity of Phyllanthus emblica to resist the scopolamine induced memory loss in male Long-Evans rats. Method: This animal behavioral study had been done on 18 male Long-Evans rats (body weight of 200-300 gm) divided into control group (normal saline 5ml/kg for 26 days), memory impaired group (scopolamine 2mg/kg for 5 days) and PE group (Phyllanthus emblica 400mg/kg for 26 days+scopolamine 2 mg/ kg for 5 days) each consisting of 6 rats. Working memory (short term) reference memory of all groups were tested by Morris Water Maze (MWM) test assessing escape latency time and target crossing. Rats of all groups were first room acclimatized for first 7 days without treatment. Then during day 8-33 normal saline EEPE (ethanolic extract of PE) was given to the respective group and during day 22-33 scopolamine was also given to the respective group. Then habituation,acquisition and probe trial was done between day 19 to day 28. In day 22-27(acquisition phase) reference memory was assessed and in day 30- 33(training and test phase) working memory was assessed. Statistical analysis was done by ANOVA followed by Bonferroni’s post hoc test. Result: Escape latency time in memory impaired group was significantly higher compared to control (normal memory) group and PE pretreated group, but there was no significant difference in escape latency time between control group and PE pretreated group. Conclusion: Phyllanthus emblica can effectively prevent scopolamine induced memory loss in Long Evans rats. J Bangladesh Soc Physiol 2024;19(2): 61-67